Identification of miR-16-5p and miR-155-5p microRNAs differentially expressed in circulating leukocytes of pregnant women with polycystic ovary syndrome and gestational diabetes. (4th March 2021) - Hocaoglu, Meryem; Demirer, Selin; Loclar Karaalp, Ilayda; Kaynak, Esra; Attar, Erkut; Turgut, Abdulkadir; Karateke, Ates; Komurcu-Bayrak, Evrim
Abstract: Introduction: Pregnant women with polycystic ovary syndrome (PCOS) are at increased risk of gestational diabetes (GDM). We aimed to assess the expressions of candidate microRNAs (miRs) in leukocytes of pregnant women with PCOS and GDM. Methods: Using real-time quantitative PCR method, miR-16-5p and miR-155-5p were examined from PCOS ( n  = 17), GDM ( n  = 14), GDM + PCOS ( n  = 11), and controls ( n  = 27). The relative expression levels of the candidate miRNAs were compared between patient and control samples. The results were calculated as relative quantification values (RQ). Results: After adjusting for potential confounding variables using ANCOVA, no significant differences were observed in miR-16-5p ( p  = .154) and miR-155-5p ( p  = .702) expressions among four groups. We found significantly upregulated miR-16-5p expression in PCOS patients (RQ = 12.97 ± 1.94; p  = .0001), compared to controls (RQ = 2.32 ± 1.46). Decreased miR-155-5p was found in GDM women (RQ = 0.80 ± 0.36; p  = .04), compared to controls (RQ = 1.78 ± 0.25). Body mass index had a positive correlation with 155-5p in the GDM group ( r  = 0.55; p  = .038). We found strong positive correlation between 1-hour glucose and miR-155-5p in PCOS patients ( r  = 0.71; p  = .001). Fasting glucose ( r = −0.63, p  = .03) presented significant inverse association with miR-16-5p in the GDM + PCOS group. Discussion: The present study shows for the first time that increased miR-16-5p expression is associated with PCOS in pregnancy. Moreover, downregulated miR-155-5p expression was found in relation with GDM.